Free water surface constructed wetlands limit the dissemination of extended-spectrum beta-lactamase producing Escherichia coli in the natural environment. (1st November 2016) - Vivant, Anne-Laure; Boutin, Catherine; Prost-Boucle, Stéphanie; Papias, Sandrine; Hartmann, Alain; Depret, Géraldine; Ziebal, Christine; Le Roux, Sophie; Pourcher, Anne-Marie
Abstract: The fates of Escherichia coli and extended-spectrum beta-lactamase-producing E. coli (ESBL E. coli ) were studied over a period of one year in a free water surface constructed wetland (FWS CW) with a succession of open water zones and vegetation ponds ( Typha or Phragmites ), that received the effluent from a wastewater treatment plant. ESBL E. coli were detected and isolated from all sampling areas of the FWS CW throughout the study period. They represented 1‰ of the total E. coli population regardless of the origin of samples. Two main factors affected the log removal of E. coli and of ESBL E. coli : the season and the presence of vegetation. Between the inlet and the outlet of the FWS CW, the log removal of E. coli ranged from 1.5 in the warmer season (summer and fall) to 3.0 in the colder season (winter and spring). The concentrations of E. coli decreased significantly in the vegetated areas during the colder season, but increased in the warmer season, suggesting an effect of the plant growth stage on the survival of E. coli . Among the 369 ESBL E. coli isolates collected during our study, 84% harbored the CTX-M-ESBL type and 55.3% carried bla genes on plasmid DNA. Furthermore, 93% of the ESBL E. coli isolates were multidrug resistant but the proportion of resistant strains did not change significantly along the FWS CW. ESBL E. coli were characterized by MLST analysis using the 7 genes based Achtman Scheme. ESBL E. coli isolated from water, sediments, roots and feces of myocastors collected in the FWS CW and in the recipient river were genotypically related, suggesting persistence and circulation of the ESBL producing E. coli throughout the FWS CW and in the receiving river. Overall, these observations show that FWS CW could be an efficient treatment for ESBL E. coli disinfection of wastewater and could limit their dissemination in the aquatic environment. Graphical abstract: Highlights: Free water surface constructed wetland reduced levels of Escherichia coli from 1.5 to 3 log. Vegetated areas increased the survival of E. coli during the warmer months. ESBL E. coli were present in all compartments of the FWS CW. ESBL E. coli carried from 1 to 4 of the bla genes both on genomic and plasmid DNA.